1992
DOI: 10.1161/01.atv.12.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoproteins inhibit endotoxin activation of monocytes.

Abstract: Human serum and low density lipoproteins (LDLs) were shown to inactivate endotoxin (lipopolysaccharide [IPS]) by testing the effect of LPS interactions with serum or LDL on the activation of human monocytes. Sera and LDL preparations from four patients with familial hypercholesterolemia were used to demonstrate the inhibition of LPS from inducing interleukin-1 release. Before LDL removal by immunoapheresis, the patients' sera were able to inactivate approximately fivefold more LPS than after LDL removal. The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 32 publications
5
20
0
Order By: Relevance
“…The in vitro data mainly parallel those found in vivo. These data confirm that binding of LPS to lipoproteins decreases its ability to activate macrophages and endothelial cells (30,57,60,196,306,366,415,554,579) (Table 5). Recently, Grunfeld et al have shown a similar inhibitory effect of lipoprotein binding on LTA-induced activation of macrophages (177).…”
Section: Anti-inflammatory Rolesupporting
confidence: 77%
“…The in vitro data mainly parallel those found in vivo. These data confirm that binding of LPS to lipoproteins decreases its ability to activate macrophages and endothelial cells (30,57,60,196,306,366,415,554,579) (Table 5). Recently, Grunfeld et al have shown a similar inhibitory effect of lipoprotein binding on LTA-induced activation of macrophages (177).…”
Section: Anti-inflammatory Rolesupporting
confidence: 77%
“…LPS predominantly binds to LDL in the circulation, which reduces its biological activity and promotes endotoxin removal. 135,[187][188][189][190][191] The data of the current study show that mild oxidation increases the endotoxin activity of LDL, maybe by altering lipid-mediated interactions between LDL and LPS. Accordingly, treatment with moxLDL but not with nLDL upregulated miR-155-5p expression in β-cells.…”
Section: Hyperlipidemia-related Endotoxemia Induces Islet Mir-155-5p mentioning
confidence: 57%
“…It has also become clear that LPS is moved into serum lipoproteins by lipid transferases, resulting in a loss of agonistic potency (9,10,13,21,31,35). E5531 is a lipophilic molecule that lacks the complex polysaccharide of LPS.…”
Section: Discussionmentioning
confidence: 99%